Federal-State regulation of the pricing and marketing of insurance - United States; MacAvoy, Paul W.; Maseritz, Guy B.; United States (Washington : American Enterprise Institute for Public Policy Research, 1977)
Early in 1975, the Gerald Ford called for an initiation of a major effort aimed at regulatory reforms. His requests set in motion agency and department initiatives, and a number of studies, reorganization proposals, and legislative proposals were forthcoming. This volumes provides one set of the analytical studies on regulatory reform that were still in process at the end of 1976.
Originally prepared as a working paper by the Antitrust Division of the Dept. of Justice. Cf. U.S. Task Group on Antitrust Immunities. Report.
"[Prepared in connection with a study conducted] at the request of the Task Force [i.e. Group] on Antitrust Immunities."
Includes bibliographical references.
ne 21/06/2018
Loans
Keywords: Insurance companies; Insurance